2012
DOI: 10.1016/j.clinph.2011.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Exploring semantic and phonological picture–word priming in adults who stutter using event-related potentials

Abstract: Objective Our aim was to investigate how semantic and phonological information is processed in adults who stutter (AWS) preparing to name pictures, following-up a report that event-related potentials (ERPs) in AWS evidenced atypical semantic picture-word priming (Maxfield et al., 2010). Methods Fourteen AWS and 14 typically-fluent adults (TFA) participated. Pictures, named at a delay, were followed by probe words. Design elements not used in Maxfield et al. (2010) let us evaluate both phonological and semant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 80 publications
(108 reference statements)
0
12
0
Order By: Relevance
“…Previous experiments in people who stutter have examined auditory processing while covertly reading (Salmelin R, Schnitzler A, Schmitz F, Jancke L, Witte OW et al, 1998), in response to ones’ own voice when speaking (Beal et al, 2010, 2011; Liotti et al, 2010) and during picture recognition and delayed production (Maxfield, Huffman, Frisch, & Hinckley, 2010; Maxfield, Pizon-Moore, Frisch, & Constantine, 2012). The studies by Maxfield et al (2010, 2012) found that long latency (> 400 ms) components related to semantic and phonological activation differed between adults who stutter and fluent controls. Taken together with the above observations, our new results indicate that auditory cortical processing can distinguish fluent men from those who stutter, and support the notion that atypical auditory processing is a prominent feature in stuttering.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments in people who stutter have examined auditory processing while covertly reading (Salmelin R, Schnitzler A, Schmitz F, Jancke L, Witte OW et al, 1998), in response to ones’ own voice when speaking (Beal et al, 2010, 2011; Liotti et al, 2010) and during picture recognition and delayed production (Maxfield, Huffman, Frisch, & Hinckley, 2010; Maxfield, Pizon-Moore, Frisch, & Constantine, 2012). The studies by Maxfield et al (2010, 2012) found that long latency (> 400 ms) components related to semantic and phonological activation differed between adults who stutter and fluent controls. Taken together with the above observations, our new results indicate that auditory cortical processing can distinguish fluent men from those who stutter, and support the notion that atypical auditory processing is a prominent feature in stuttering.…”
Section: Discussionmentioning
confidence: 99%
“…This experiment was conducted in the same facility as our previous work (Maxfield et al, 2010, 2012, 2015), thus involving many of the same recording tools and settings. The experiment took place in a sound-attenuating booth contained within a laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…As reviewed in (Maxfield, 2015; Maxfield et al, 2010, 2012, 2014), psycholinguistic research has produced some evidence that both lexical-semantic and phonological processing may operate differently in AWS versus TFA, including evidence that these processes may be atypically resource-demanding in AWS. For example, some studies using word association, picture naming, vocabulary and other relatively simple language production tasks have produced evidence that the accuracy or efficiency with which AWS retrieve conceptually-appropriate words may be diminished (Crowe and Kroll, 1991; Wingate, 1988; Newman and Ratner, 2007; Pellowski, 2011; Watson et al, 1994; Bosshardt and Fransen, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations